SOCIETY, LAND AND POWER IN THE UNITED STATES OF COLOMBIA, 1857-1885: THE CASE OF THE SOVEREIGN STATE OF BOLIVAR - Solano D, Sergio Paolo (2013)
This article discusses some aspects of the process of appropriation of public land (wastelands and ejidos) and private in Colombia Federal period (1857-1885), the resources used by those interested in that purpose, geographic and economic rationality of such appropriations and instrumentalization of the state held by some stakeholders in the land. Our analysis rests on the idea of recovering the prominence it is acquiring the social sectors-State relationship in accordance with the circumstances of the towns and provinces that comprised the Sovereign State of Bolívar then.